Wide band multi stage eight way Wilkinson power divider for defense applications - Siva Charan, M; Rajasekhar, A; V. Venkateswara Rao, K; Lakshmi Prasanna, Ch; Vummadisetty. Naidu, Praveen; Bansod, Gaurav; Kumar, Arvind (International Journal of Engineering and Technology, 2018)
In this paper, a compact 8 way microstrip line Wilkinson Power Divider (WPD) is designed and proposed. The equal power divider con-sists of multiple multi-section WPDâ€™s with isolation resistors. By utilizing the multi-sections concept, a remarkably increase in the band-width is observed. In the design process, RT 5880 substrate is used with the thickness of 0.8 mm and dielectric constant of 2.2 and loss tangent of 0.0004. The simulated results such as return loss, insertion loss and isolation are plotted by using ADS simulation software and obtained results show good agreement. Â